Small-molecule BH3 mimetic and pan-Bcl-2 inhibitor AT-101 enhances the antitumor efficacy of cisplatin through inhibition of APE1 repair and redox activity in non-small-cell lung cancer - Ren T; Shan J; Li M; Qing Y; Qian C; Wang G; Li Q; Lu G; Li C; Peng Y; Luo H; Zhang S; et al. (Dove Medical Press, 2015)
Tao Ren,1–3,* Jinlu Shan,1,* Mengxia Li,1 Yi Qing,1 Chengyuan Qian,4 Guangjie Wang,5 Qing Li,1,3 Guoshou Lu,1 Chongyi Li,1 Yu Peng,1 Hao Luo,1 Shiheng Zhang,1 Yuxing Yang,1 Yi Cheng,1 Dong Wang,1 Shu-Feng Zhou31Cancer Center, Daping Hospital and Research Institute of Surgery, Third Military Medical University, Chongqing, 2Department of Oncology, The Affiliated Hospital, North Sichuan Medical College, Sichuan, People’s Republic of China; 3Department of Pharmaceutical Sciences, College of Pharmacy, University of South Florida, Tampa, FL, USA; 4Department of Oncology, The 97 Hospital of PLA, Jiangsu, 5Cancer Diagnosis and Treatment Center, Military District General Hospital of Chengdu Military Region, Sichuan, People’s Republic of China*These authors contributed equally to this workAbstract: AT-101 is a BH3 mimetic and pan-Bcl-2 inhibitor that has shown potent anticancer activity in non-small-cell lung cancer (NSCLC) in murine models, but failed to show clinical efficacy when used in combination with docetaxel in NSCLC patients. Our recent study has demonstrated that AT-101 enhanced the antitumor effect of cisplatin (CDDP) in a murine model of NSCLC via inhibition of the interleukin-6/signal transducer and activator of transcription 3 (STAT3) pathway. This study explored the underlying mechanisms for the enhanced anticancer activity of CDDP by AT-101. Our results show that, when compared with monotherapy, AT-101 significantly enhanced the inhibitory effects of CDDP on proliferation and migration of A549 cells and on tube formation and migration in human umbilical vein endothelial cells. AT-101 promoted the proapoptotic activity of CDDP in A549 cells. AT-101 also enhanced the inhibitory effect of CDDP on DNA repair and redox activities of apurinic/apyrimidinic endonuclease 1 (APE1) in A549 cells. In tumor tissues from nude mice treated with AT-101 plus CDDP or monotherapy, the combination therapy resulted in greater inhibition of angiogenesis and tumor cell proliferation than the monotherapy. These results suggest that AT-101 can enhance the antitumor activity of CDDP in NSCLC via inhibition of APE1 DNA repair and redox activities and by angiogenesis and induction of apoptosis, but other mechanisms cannot be excluded. We are now conducting a Phase II trial to examine the clinical efficacy and safety profile of combined use of AT-101 plus CDDP in advanced NSCLC patients.Keywords: AT-101, cisplatin, non-small-cell lung cancer, apurinic/apyrimidinic endonuclease 1, angiogenesis, tumor